Advances in Digital Cultural Heritage - (:unkn) unknown (My University, 2018)
This book constitutes the papers of the International Workshop on Analysis in Digital Cultural Heritage 2017, held in Funchal, Madeira, Portugal, in June 2017. The 16 full and 19 poster papers were carefully reviewed and selected from 93 submissions. The main objective of the Workshop was to present recent developments and applications of IT technologies for Cultural Heritage preservation, namely: Demonstration of the advantages of new generation of equipment for mapping, digital survey and documentation of heritage assets and sites; Presentation of technologies for digitalization, optimal documentation and information sharing on Cultural Heritage; Tools and procedures for social interaction enhancing, fostering awareness and participation; Rising of the knowledge level in domain of IT applications for Cultural Heritage preservation; Usage of virtual reality for better understanding and learning on Cultural Heritage.
Keywords: Cultural heritage; 3D imaging; Artificial intelligence; Augmented reality; Computer vision; Digital libraries and archives; Human-centered computing; Image reconstruction